The Relationship Between Waiting Time and Patient Satisfaction at the Nikel Polyclinic of X Hospital, East Jakarta, 2025 - Rusmiyati, Endang; Wiharto, Mulyo (Sean Institute, 2025)
This study investigates the relationship between waiting time for health services and patient satisfaction in the outpatient department of a hospital in East Jakarta. Patient satisfaction is considered an essential indicator of service quality and overall performance in health care institutions. Excessive waiting time often becomes one of the main complaints from patients and can negatively influence their perception of the quality of care received. Using a cross-sectional design with a quantitative approach, the research examines whether prolonged waiting time is associated with decreased satisfaction among patients receiving outpatient services. Data were collected through structured questionnaires and analyzed to identify the strength and direction of the relationship. The findings indicate that waiting time plays a significant role in shaping patient satisfaction, suggesting that efforts to minimize delays are crucial for improving health care delivery, enhancing patient experience, and strengthening institutional credibility.